Pendampingan Pelestarian Budaya dan Nilai-Nilai Kearifan Lokal pada Kenduri Pasca Panen Raya - Edy Saputra; Zuhriyandi; Syaliman; Aida Munawarah; Noer Shalehatun; Nikmah Maharani; Rahmani; Laina Widia; Haida Roudatun Nisa (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2023)
The Post-Harvest Kenduri tradition which is carried out every year is a form of preserving culture and local wisdom values ​​in Pasir Village, Gayo Lues Regency. This article was written based on the results of a study of assistance provided by the author to the Kampung Pasir community. The aim of this service is to provide ideas so that the younger generation in particular can play an active role in efforts to preserve and maintain the local cultural values ​​of Kampung Pasir. The approach used during service is Participation Action Research (PAR) to apply knowledge and apply theory to the general public. The results of the service show that the Post-Harvest Kenduri ceremony which has been carried out by the people of Pasir village from the past until now aims to give thanks to Allah SWT who has bestowed grace and gifts on the community, both the blessings of life and good fortune. The people of Kampung Pasir can maintain this Kenduri tradition by including positive activities, including facilitating friendship between village residents and preserving the historical values ​​of the past. It is hoped that this post-harvest kenduri tradition will be maintained and passed down to the younger generation from generation to generation.